Increasing the motivation of madrasah Aliyah students to learn cross-interest English subject by applying the game “relay race” - Annafiah, Afiya Ulin Nuha (Universitas Muhammadiyah Malang, 2024)
Cross-interest subjects are programs and policies from the government that aim to provide opportunities for students to choose and study subjects that are not in the specialization program so that they will add insight, experience, and knowledge that they have later. In theory, students should have a high motivation or enthusiasm for learning to study the cross-interest subjects they have chosen. However, the facts in the classroom show the opposite. This study aims to increase student learning motivation in English Cross Interest subjects in class XI MIPA Madrasah Aliyah Negeri Kota Batu through the application of a